A cascade dual-targeted nanocarrier for enhanced alectinib delivery to ALK-positive lung cancer. (13th October 2020) - Zeng, Fanjun; Xu, Bin; Zhu, Hongyuan; Wu, Shaowei; Liao, Guoqing; Xie, Daipeng; Huang, Luyu; Qiao, Guibin; Yang, Xianzhu; Zhou, Haiyu
Abstract : A polymeric nanocarrier with a cascade of magnetic and TAT targeting enhanced the therapeutic efficacy of alectinib towards ALK-positive lung cancer. Abstract : Alectinib is a highly efficacious inhibitor for the treatment of anaplastic lymphoma kinase (ALK)-positive non-small cell lung cancer (NSCLC) in the clinic; however, serious adverse events (AEs) occurred in 44.0% of patients. Herein, we explored magnetic/TAT dual-targeted nanocarriers as delivery systems for alectinib. Magnetic targeting efficiently enhanced the extravasation of alectinib-loaded nanoparticles from vessels into the tumor tissue, while the TAT targeting reactivated in the tumor tissue significantly improved the tumor cellular uptake of the nanocarrier. As a result, this dual-targeted polymeric nanocarrier exhibited superior therapeutic effects and induced tumor shrinkage in vivo . Meanwhile, this dual-targeted nanocarrier also minimized alectinib-induced hepatotoxicity, providing an efficient strategy to extend the application of alectinib for NSCLC patients.